The Impact of the Interactivity of Internet Celebrity Anchors on Consumers’ Purchase Intention - Sun, Weiguo; Gao, Wei; Geng, Ruoshi (Frontiers in Psychology, 2021)
The current study focuses on a novel and recently popular internet phenomenon – celebrity livestreaming marketing. As one of the primary advantages of livestreaming marketing by Internet celebrities, we propose that the timely interactivity of Internet celebrities plays an important role in consumers’ purchase intention. Based on stimulus-organism-response (SOR) theory, this paper further identifies social presence and flow experience as mediators and the consistency of Internet celebrities’ image and product image as a moderator and constructs an influence model of Internet celebrities’ interactivity on consumers’ purchase intention. The responses of a sample of 277 participants were collected by questionnaire survey. SPSS and Amos were used to analyse the data. The results show that consumers’ social presence and flow experience mediate the positive impact of the interactivity of Internet celebrity anchors on influencing consumers’ purchase intention. However, there is no significant moderating effect of the consistency of Internet celebrities’ image and product image on the relationship between social presence or flow experience and purchase intention. A discussion and implications are offered.